2019
DOI: 10.1016/j.memsci.2019.117333
|View full text |Cite
|
Sign up to set email alerts
|

Layered composite membranes based on porous PVDF coated with a thin, dense PBI layer for vanadium redox flow batteries

Abstract: A commercial porous polyvinylidene fluoride membrane (pore size 0.65 μm, nominally 125 µm thick) is spray coated with 1.2 -4 µm thick layers of polybenzimidazole. The area resistance of the porous support is 36.4 mΩ cm 2 in 2M sulfuric acid, in comparison to 540 mΩ cm 2 for a 27 µm thick acid doped polybenzimidazole membrane, and 124 mΩ cm 2 for PVDF-P20 (4 µm thick blocking layer). Addition of vanadium ions to the supporting electrolyte increases the resistance, but less than for Nafion. The expected reason i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(27 citation statements)
references
References 37 publications
1
26
0
Order By: Relevance
“…A large number of publications have focused on membranes for RFBs [ 2 , 3 , 4 ], where researchers proposed new designs and materials to increase stability and efficiency in this storage technology during prolonged charge/discharge cycling. Recent studies showed membranes consisting of an asymmetric architecture [ 5 , 6 , 7 ] and others comprising a porous support coated with a thin polymer layer to act as a barrier against the crossover of electroactive species (e.g., vanadium or organic molecules) [ 8 , 9 , 10 ]. Furthermore, the membrane design can become relevant on a technical scale in terms of investment costs.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of publications have focused on membranes for RFBs [ 2 , 3 , 4 ], where researchers proposed new designs and materials to increase stability and efficiency in this storage technology during prolonged charge/discharge cycling. Recent studies showed membranes consisting of an asymmetric architecture [ 5 , 6 , 7 ] and others comprising a porous support coated with a thin polymer layer to act as a barrier against the crossover of electroactive species (e.g., vanadium or organic molecules) [ 8 , 9 , 10 ]. Furthermore, the membrane design can become relevant on a technical scale in terms of investment costs.…”
Section: Introductionmentioning
confidence: 99%
“…Recently,K won, Henkensmeier et al coated thin PBI layers on ap orous PVDF substrate by as praycoating method for VRFBs. [96] As the number of PBI layers increased, the defects on the skin layer disappeared. Although the AR also increased, it was still rationally lower than the homogeneous counterparts.Anotable finding of this work is that the orientation of the PBI layer had ahuge effect on vanadium permeability.W hent he PBI layer faced the vanadium-rich side,t he vanadium permeability lower than the value when the PBI layer faced the vanadium-lean side.…”
Section: Uncharged Channels In Composite/hybrid Membranesmentioning
confidence: 99%
“…demonstrated an impressively high chemical stability of the PBI porous membrane in VFBs (>13 000 cycles at current densities ranging from 80 to 120 mA cm −2 ). Due to its prominent properties, PBI has been reported as the top layer on Nafion, poly(vinylidene difluoride), and PE . Jung et al .…”
Section: Composite Membranes In Fb Applicationmentioning
confidence: 99%